2023
DOI: 10.1182/bloodadvances.2022008854
|View full text |Cite
|
Sign up to set email alerts
|

Association of TIM-3 checkpoint receptor expression on T cells with treatment-free remission in chronic myeloid leukemia

Abstract: Dysregulation of immune checkpoint receptors has been reported at diagnosis of chronic myeloid leukemia (CML), but their role in the maintenance of remission after tyrosine kinase inhibitor (TKI) cessation is unclear. We assessed PD-1, TIM-3, CTLA-4, LAG-3 and TIGIT expression on T-cell subsets, regulatory T cells (T-regs), and natural killer (NK) cells at the time of TKI cessation in 44 patients (22 who sustained treatment-free remission (TFR), 22 who experienced molecular relapse (MolR)). We confirmed our pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
2
3
0
Order By: Relevance
“…We also identified significant cell surface overexpression of TIM3 when comparing CML LSC with normal HSC, which is in line with a previous report showing upregulated TIM3 gene expression ( HAVCR2 ) in CML LSC based on mining of publicly available RNA-seq datasets 29 . In addition, TIM3 is reportedly overexpressed and critical for self-renewal of LSC in acute myeloid leukemia (AML) 23,24,30 .…”
Section: Discussionsupporting
confidence: 91%
“…We also identified significant cell surface overexpression of TIM3 when comparing CML LSC with normal HSC, which is in line with a previous report showing upregulated TIM3 gene expression ( HAVCR2 ) in CML LSC based on mining of publicly available RNA-seq datasets 29 . In addition, TIM3 is reportedly overexpressed and critical for self-renewal of LSC in acute myeloid leukemia (AML) 23,24,30 .…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, blocking of TIM3 in the co-culture assays also led to increased IFN-γ secretion although no clear effect on target cell killing was seen. A recent study identified elevated HAVCR2 /TIM3 in CD8 + T cells from patients with relapse following TKI withdrawal [ 51 ] as we noted in our PR1-specific CD8 + T cells. As such, immune-checkpoint inhibitors targeting TIGIT and TIM3 are interesting molecular targets to induce more potent NK cell engagement against CML cells, but further studies are needed with larger cohort of primary CML cells.…”
Section: Discussionsupporting
confidence: 84%
“…Immune suppressors including T-regs and monocytic MDSCs have been shown to play a critical role in successful TFR. 9,50,51 Our data demonstrate that addition of IFN to nilotinib does not alter the downward trajectory of immune suppressors from diagnosis to DMR.…”
Section: Discussionmentioning
confidence: 68%
“…Here we show MDSCs rapidly decreased following nilotinib therapy, likely due to targeting of BCR::ABL1 ‐positive MDSCs by TKI, 49 and were not affected by the addition of IFN, remaining at low‐level long term. Immune suppressors including T‐regs and monocytic MDSCs have been shown to play a critical role in successful TFR 9,50,51 . Our data demonstrate that addition of IFN to nilotinib does not alter the downward trajectory of immune suppressors from diagnosis to DMR.…”
Section: Discussionmentioning
confidence: 71%